Carbon lost and carbon gained: a study of vegetation and carbon trade‐offs among diverse land uses in Phoenix, Arizona. Issue 2 (7th March 2017) - McHale, Melissa R.; Hall, Sharon J.; Majumdar, Anandamayee; Grimm, Nancy B.
Abstract: Human modification and management of urban landscapes drastically alters vegetation and soils, thereby altering carbon (C) storage and rates of net primary productivity (NPP). Complex social and ecological processes drive vegetation cover in cities, leading to heterogeneity in C dynamics depending on regional climate, land use, and land cover. Recent work has demonstrated homogenization in ecological processes within human‐dominated landscapes (the urban convergence hypothesis) in soils and biotic communities. However, a lack of information on vegetation in arid land cities has hindered an understanding of potential C storage and NPP convergence across a diversity of ecosystem types. We estimated C storage and NPP of trees and shrubs for six different land‐use types in the arid metropolis of Phoenix, Arizona, USA, and compared those results to native desert ecosystems, as well as other urban and natural systems around the world. Results from Phoenix do not support the convergence hypothesis. In particular, C storage in urban trees and shrubs was 42% of that found in desert vegetation, while NPP was only 20% of the total NPP estimated for comparable natural ecosystems. Furthermore, the overall estimates of C storage and NPP associated with urban trees in the CAP ecosystem were much lower (8–63%) than the other cities included in this analysis. We also found that C storage (175.25–388.94 g/m 2 ) and NPP (8.07–15.99 g·m −2 ·yr −1 ) were dominated by trees in the urban residential land uses, while in the desert, shrubs were the primary source for pools (183.65 g/m 2 ) and fluxes (6.51 g·m −2 ·yr −1 ). These results indicate a trade‐off between shrubs and trees in arid ecosystems, with shrubs playing a major role in overall C storage and NPP in deserts and trees serving as the dominant C pool in cities. Our research supports current literature that calls for the development of spatially explicit and standardized methods for analyzing C dynamics associated with vegetation in urbanizing areas.